Medo de COVID-19, insegurança alimentar e ansiedade em mulheres usuárias do SUS na cidade de João Pessoa - PB - Freire, Flora Luiza Pereira do Nascimento (2022)
With the declaration of a coronavirus pandemic in March 2020, sudden changes took place in living standards which altered routine, limiting all types of face-to-face relationships, requiring quarantine, closing public places and mandatory use of masks. All the changes imposed abruptly in order to slow the spread of the virus increased fear and produced negative results for mental health, especially in women, due to their vulnerability from a socioeconomic and mental point of view. This study aimed to describe the perceptions of fear caused by the COVID-19 pandemic, according to the conditions of food insecurity and anxiety, and to analyze the association of food insecurity and fear of COVID-19 as predictors of anxiety in women using the SUS, residents in the municipality of João Pessoa. This is a cross-sectional study, carried out in 2021, with women users of the Unified Health System - SUS in João Pessoa - PB. The assessment of the food (in)security situation was carried out using the Brazilian Food Insecurity Scale, state anxiety through the state anxiety inventory, fear of COVID-19 through the COVID-19 Fear Scale. Descriptive analysis of all variables was performed and relationships between variables were observed using the chi-square or Fisher's exact association tests. The 73 women interviewed had a median per capita income of R$665.33, had a median age of 33 years, 58.9% lived with a partner, 56% declared themselves to be black/brown, 55% had completed high school or higher education, and 60.3% lived in houses with up to 3 residents. In this study, fear of COVID-19 was predictive of anxiety (OR = 3.167; 1.003 – 10.778), and AI was related to fear of COVID-19 (p=0.010). The present study brought to light data that demonstrate that the current pandemic contributed to the increase in anxiety, an important fact for the development of public policies aimed at caring for the integral health of women in the current context of the coronavirus pandemic.